PERKEMBANGAN PEMIKIRAN DALAM AKHLAK ISLAM - Abdul Wahab Syakhrani; Esva Maulida; Laila Laila (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
History of the Development of Morals In the Greek Age, Socrates was seen as the pioneer of the Science of Morals. He believes that morals and forms of communication do not become true unless they are based on science. Then came Plato (427-347 BC). He was an Athenian philosopher, who was a student of Socrates. His thoughts in Ethics are based on 'the theory of examples'. He argues that other realms are spiritual realms. Then followed by Aristotle (394-322 BC), he was Plato's student. His followers were called Peripatetis because he gave lessons while walking or on a shady promenade.